2015
DOI: 10.1007/s13204-014-0396-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical synthesis, characterisation and phytogenic properties of silver nanoparticles

Abstract: This work exemplifies a simple and rapid method for the synthesis of silver nanodendrite with a novel electrochemical technique. The antibacterial activity of these silver nanoparticles (Ag NPs) against pathogenic bacteria was investigated along with the routine study of optical and spectral characterisation. The optical properties of the silver nanoparticles were characterised by diffuse reflectance spectroscopy. The optical band gap energy of the electrodeposited Ag NPs was determined from the diffuse reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 53 publications
3
45
0
Order By: Relevance
“…K = 0.89 is the Debye–Scherrer constant. The lattice strain, ε, were estimated using the Williamson–Hall (WH) plot, determined according to Singaravelan and Alwar ( 2015 ) using the following equation (Eq. 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…K = 0.89 is the Debye–Scherrer constant. The lattice strain, ε, were estimated using the Williamson–Hall (WH) plot, determined according to Singaravelan and Alwar ( 2015 ) using the following equation (Eq. 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the UV–visible absorption spectrum of Ag is closely connected with its structure and can directly reflect the size and shape of Ag NPs . According to Mie theory, spherical Ag NPs exhibit a single absorption peak; however, Ag NPs of other shapes, such as rods, triangles, dendrites and prisms, show two or three absorption peaks.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the UV-visible absorption spectrum of Ag is closely connected with its structure and can directly reflect the size and shape of Ag NPs. [30,31] According to Mie theory, spherical Ag NPs exhibit a single absorption peak; however, Ag NPs of other shapes, such as rods, triangles, dendrites and prisms, show two or three absorption peaks. Thus, the single peak at 422 nm of MWNT-Ag illustrates that Ag NPs on the surface of MWNTs have a spherical shape, which is in agreement with the analysis of the FE-SEM images of MWNT-Ag.…”
Section: Uv-visible Absorption Spectramentioning
confidence: 99%
“…In this study, the optical bandgap (Eg) of the as-prepared nanoparticles was determined using the Kubelka-Munk method (Singaravelan & Alwar, 2015). The optical bandgap energy was calculated according to the Tauc equation (Tauc, 1968), which can be expressed as follows:…”
Section: Optical Bandgap Measurementmentioning
confidence: 99%
“…Measurement of optical bandgap has been considered one of the key factors in determining the potential applicability of a particular semiconducting material such as TiO2 in various types of applications, including photocatalysis. Typically, highly crystalline anatase TiO2 nanoparticles would have a bandgap value in the range of ~3.2 (Singaravelan & Alwar, 2015). Nevertheless, recent studies have also reported that several factors, such as the crystallinity, presence of impurities, crystal defects, nanoparticle grain size, and oxygen deficiencies could often alter the bandgap value of a typical semiconducting material such as TiO2 (Hidalgo et al, 2007).…”
Section: Effect Of Au-tio2 Integration On Bandgapmentioning
confidence: 99%